Credibility of social media influencers: Impact on purchase intention - Coutinho, F. (2023)
Nowadays a lot of companies use social media influencers as a marketing strategy. They are a tool for any emerging company that wants to increase consumer numbers of a specific target audience, effective for several generations. This research focuses on examining brand equity and consumers’ attitude and purchase intentions depending on credibility, measured as the expertise, trustworthiness, and attractiveness of social media influencers. To study these variables, a study hypothesis was made using the PSL-SEM model based on a measured questionnaire. The obtained results suggest that both credibility of social media influencers and brand equity have a positive impact on consumers’ purchase intentions and they are positively interrelated. These results also make it possible to infer that although the independent variable, trustworthiness, does not directly influence brand equity, it has indirect impact through other variables.